2007
DOI: 10.1007/s00248-007-9216-3
|View full text |Cite
|
Sign up to set email alerts
|

Culturable Airborne Bacteria in Outdoor Environments in Beijing, China

Abstract: Airborne bacteria are important biological components of bioaerosol and play an important role in ecosystem. Bacteria at a high concentration in the atmosphere can result in biological air pollution and all kinds of diseases. In this study, a systematical survey on the culturable airborne bacteria was carried out for 1 year at three sites in Beijing urban area. Results showed that concentrations of culturable bacteria ranged from 71 colony forming units (CFU)/m(3) to 22,100 CFU/m(3), and the mean was 2,217 CFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
148
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(168 citation statements)
references
References 34 publications
17
148
2
1
Order By: Relevance
“…This is attributed to the absence of direct human disturbances, and good natural ventilation. Generally microbial concentrations in the urban environment are influenced by human activities 40 , and their composition varies in different cities 41 .In the present study there were unclear correlations found between airborne microorganisms and meteorological factors. This is attributed to the influence of irregular disturbances and human activities, which may have more influence on microbial concentrations than meteorological factors near the holy mosque.…”
Section: Discussioncontrasting
confidence: 54%
“…This is attributed to the absence of direct human disturbances, and good natural ventilation. Generally microbial concentrations in the urban environment are influenced by human activities 40 , and their composition varies in different cities 41 .In the present study there were unclear correlations found between airborne microorganisms and meteorological factors. This is attributed to the influence of irregular disturbances and human activities, which may have more influence on microbial concentrations than meteorological factors near the holy mosque.…”
Section: Discussioncontrasting
confidence: 54%
“…Culturing methods in general find more Gram-positive bacteria (e.g. Mancinelli and Shulls, 1978;Atlas and Bartha, 1997;Atlas and Bartha, 1997;Fuzzi et al, 1997;Kellogg and Griffin, 2006;Amato et al, 2007b;Fang et al, 2007;Fahlgren et al, 2010), whereas culture-independent techniques primarily find Gram-negative bacteria (e.g. Radosevich et al, 2002;Maron et al, 2005;Brodie et al, 2007;Despre´s et al, 2007;Fierer et al, 2008;Fahlgren et al, 2010).…”
Section: Bacteria and Archaeamentioning
confidence: 99%
“…Bacterial diversity in rural areas is generally higher than at urban sites (Despre´s et al, 2007). Still, the concentration of bacteria seems often to be higher in urban than in rural environments (Bovallius et al, 1978;Chihara and Someya, 1989;di Giorgio et al, 1996;Shaffer and Lighthart, 1997;Fang et al, 2007;Fahlgren et al, 2010), even when the samples are taken in the same geographic region. However, opposite trends have also been found: For example, Rosas et al (1993) described that bacterial concentrations in rural environments are higher than in urban sites.…”
Section: Bacteria and Archaeamentioning
confidence: 99%
See 2 more Smart Citations